PENGARUH LKS TERINTEGRASI NILAI KARAKTER DALAM MODEL ICARE TERHADAP KOMPETENSI IPA SISWA KELAS VII SMPN 35 PADANG - Najmiatul Fajri; Ratnawulan Ratnawulan; Syafriani Syafriani (PILLAR OF PHYSICS EDUCATION, 2016)
The student competence consists of knowledge, attitudes and skills. Competence is expexted to be reached after learning. In fact, the achievement of competence is not optimal. One of the causes is the lack of the student’s motivation. The solution of this problem is by using integrated student worksheetof character values in the ICARE model. It is expected to engender the motivation of learning as well as the change of the student’s attitude to be better. The purpose of this research is to know the influence of the use of LKS integrated character values in the ICARE model towards the competence of science students grade VIIat SMPN 35.This type of research was quasi experiment using randomized control group only design. The population of this research were all the students grade VII at SMPN 35  Padangwhich were registered in the Academic Year of 2015/2016. The technique of purposive sampling was used to collect the sample. The research data consist of knowledge, spiritual attitudes, social attitudes and skills.The collected data were analized by using Chi Square at significance level of 0.05 and dk 1. Based on the data analysis, it can be concluded that the using of integrated student worksheet of character values in the ICARE model gives means influence toward to the competence of science students grade VII at SMPN 35 Padang.